ECOLOGICAL AND LEGAL REQUIREMENTS OF USE AND PROTECTION OF UNDERGROUND RESOURCES IN THE REPUBLIC OF UZBEKISTAN - A. B. Janzakov; F. M. Mutalov (Scholar Express Journal, 2024)
In this article, the study of ecological and legal information on the natural resources of Uzbekistan is given in the law on the use of underground resources and nature protection
Keywords: underground resources; environmental law; foreign investors